Disseminated Intravascular Coagulation - Levi, Marcel; de Jonge, Evert; van der Poll, Tom; ten Cate, Hugo (Thrombosis and Haemostasis, 1999)
A quick literature search in the MEDLINE databases from 1966 to 1998 using the search term disseminated intravascular coagulation (DIC) and related key words yields an impressive 11,921 manuscripts. Most of the published literature concerns the pathophysiology of DIC, which in its main features is now well understood. Other aspects of DIC, however, particularly those related to the definition, the relevance of the syndrome, and clinical management, remain unclear. Taking an evidence-based approach to the appropriate diagnosis and treatment of patients with DIC is difficult, in view of the lack of sound clinical trials. This is probably due to the fact that DIC is a poorly-defined syndrome with a widely variable intensity, often complicating a diversity of severe disorders that are themselves related to extensive morbidity and mortality.1,2 This chapter briefly reviews the clinical setting, incidence, and relevance of DIC and current insights into the pathogenesis of DIC. It also discusses the available knowledge on the clinical management of patients with this syndrome.DIC is not a disease or a symptom but rather a syndrome, which is always secondary to an underlying disorder. The syndrome is characterized by a systemic activation of the blood coagulation system, which results in the generation and deposition of fibrin, leading to microvascular thrombi in various organs and contributing to the development of multiorgan failure. Consumption and subsequent exhaustion of coagulation proteins and platelets, due to the ongoing activation of the coagulation system, may induce severe bleeding complications, although microclot formation may occur in the absence of severe clotting factor depletion and bleeding.3 Derangement of the fibrinolytic system further contributes to intravascular clot formation (discussed later), but in some cases accelerated fibrinolysis (e.g., due to consumption of α2-antiplasmin) may cause severe bleeding. Hence, a patient with DIC can present with simultaneous thrombotic and bleeding problems, which obviously complicates treatment. Although there is no general consensus regarding the definition of DIC, the definition as put forward by Müller-Berghaus and colleagues in 1995 might be most appropriate: “Disseminated intravascular coagulation is an acquired syndrome characterized by the activation of intravascular coagulation up to intravascular fibrin formation. The process may be accompanied by secondary fibrinolysis or inhibited fibrinolysis.”4